Implementasi Kebijakan Penguatan Pendidikan Karakter di Sekolah - Nabila Azrilia Syahra; Tsania Tazlila Wardhani; Chadiza Azzahra; Muhammad Iqbal Ramadhan (Reflection : Islamic Education Journal, 2025)
Education is a strategic effort to overcome ignorance and poverty, which remain serious problems in Indonesia. Through education, individuals can acquire knowledge, skills, and a broad understanding of the world, thereby improving their quality of life and contributing to the nation's progress. Quality education will create superior, independent, and competitive human resources in the era of globalization. In this article, the author attempts to examine issues related to the implementation of education in schools through a qualitative approach. The research was conducted using several methods, namely observation, interviews, and field notes. Observations were conducted directly in the school environment to thoroughly understand the context being studied, including interactions between school members and the implementation of the learning process. Furthermore, interviews were used to gather information from informants, such as teachers, students, and school staff, to gain a deeper insight into the realities of education on the ground. Meanwhile, field notes were used as a tool for documentation and reflection on the results of the observations and interviews, which later became the basis for knowledge discovery and theory strengthening. The simultaneous use of these three methods enabled the author to obtain rich and in-depth data. This research shows that in the implementation of education still face several obstacles, such as limited facilities, lack of training for educators, and suboptimal parental involvement. Therefore, the implementation of education must be carried out through careful planning, appropriate strategies, and collaboration between various parties in order to achieve educational goals effectively and sustainably.